PENGENALAN METODE INQUIRI DALAM PEMBELAJARAN IPA DI SDN 6 UBUNG DENPASAR N. Wendri1) dan M. Susilawati2) - N. Wendri; M. Susilawati (Buletin Udayana Mengabdi, 2013)
Technological developments will not be separated from the development in the field of Natural Sciences (IPA).Development of the field of science is not likely to occur if not accompanied by an increase in the quality of scienceeducation. Moreover, it has been considered that teaching science is as a difficult subject. Inquiri is a learningprocess based on the search and discovery through systematic thinking process. This activity was done in SDN 6Ubung Denpasar on fourth grade students. This activity aims to improve the understanding of materials sciencein the fourth grade students of SDN 6 Ubung Denpasar and increase student interaction in the classroom inattending the learning science. IPA materials covered are the parts of the plant. Analysis results obtained mean= 71.79 indicating that the average student evaluation results for the discussion of the parts of the plants is 71.79,this score is greater than the average score of the specified class, which is 65. T-test results also showed t = 4.40with p = 0.000 smaller 0.05. This means learning implemented effectively enhance students’ understanding andknowledge of the science subjects.